Fast response of carbon monoxide gas sensors using a highly porous network of ZnO nanoparticles decorated on 3D reduced graphene oxide - Ha, Nguyen Hai; Thinh, Dao Duc; Huong, Nguyen Thanh; Phuong, Nguyen Huy; Thach, Phan Duy; Hong, Hoang Si (Applied surface science, 2018)
•Novel CO gas sensor with ZnO/3D-RGO integrated on micro-heater.•Large amount and simple synthesis of ZnO/3D-RGO by hydrothermal method.•Enhance response/recovery time and low concentration detectable (<10 ppm) of CO sensor.•Fast response/recovery time of CO sensor less than ten seconds at working temperature of 200 oC. Zinc oxide (ZnO) nanoparticles loaded onto 3D reduced graphene oxide (3D-RGO) for carbon monoxide (CO) sensing were synthesized using hydrothermal method. The highly porous ZnO/3D-RGO configuration was stable without collapsing and was deposited on the micro-heater of the CO gas sensor. The resulting CO gas sensor displayed high sensitivity, fast response/recovery, and good linearity. The sensor achieved a response value of 85.2% for 1000 ppm CO at a working temperature of 200 °C. The response and recovery times of the sensor were 7 and 9 s for 1000 ppm CO at 200 °C. Similarly, the response value, response time, and recovery time of the sensor at room temperature were 27.5%, 14 s, and 15 s, respectively. The sensor demonstrated a distinct response to various CO concentrations in the range of 1–1000 ppm and good selectivity toward CO gas. In addition, the sensor exhibited good repeatability in multi-cycle and long-term stability.